Bioactive decellularized cardiac extracellular matrix-based hydrogel as a sustained-release platform for human adipose tissue-derived stromal cell-secreted factors - Liguori, Tácia Tavares Aquinas; Liguori, Gabriel Romero; van Dongen, Joris A; Moreira, Luiz Felipe Pinho; Harmsen, Martin Conrad (Biomedical materials (Bristol), 2021)
The administration of trophic factors (TFs) released by mesenchymal stromal cells (MSCs) as therapy for cardiovascular diseases requires a delivery vehicle capable of binding and releasing the TF in a sustained manner. We hypothesized that hydrogels derived from cardiac decellularized extracellular matrix (cardiac dECM) bind MSC secretome-derived TF and release these in a sustained fashion. Pig-derived ventricular tissue was decellularized, milled to powder, digested, and assembled as a hydrogel upon warming at 37 °C. The conditioned medium (CMed) of adipose tissue-derived stromal cells (ASC) was collected, concentrated, and incorporated into the hydrogel at 1×, 10×, and 100× the original concentration. The release of 11 ASC-secreted factors (angiopoietin-1, angiopoietin-2, fibroblast growth factor-1, hepatocyte growth factor, platelet-derived growth factor-AA, vascular endothelial growth factor, interleukin-1β, interleukin-6, interleukin-8, CCL2, and matrix metalloproteinase-1) from hydrogels was immune assessed. Bioactivity was determined by endothelial cell proliferation, function, and assessment of endothelial mesenchymal transition. We showed that dECM hydrogels could be loaded with human ASC-secreted TFs, which are released in a sustained manner for several days subsequently. Different trophic factors had different release kinetics, which correlates with the initial concentration of CMed in the hydrogel. We observed that the more concentrated was the hydrogel, the more inflammation-related cytokines, and the less pro-regenerative TFs were released. Finally, we showed that the factors secreted by the hydrogel are biologically active as these influence cell behavior. The use of dECM hydrogels as a platform to bind and release paracrine factors secreted by (mesenchymal) cells is a potential alternative in the context of cardiovascular regeneration.